Have Tumor Suppressor PDCD4 and its Counteragent Oncogenic miR-21 Gone Rogue? - Young, Matthew R. (American Society for Pharmacology and Experimental Therapeutics, 2010)
A recent article suggests that the well known tumor suppressor PDCD4 also functions as a pro-inflammatory agent. The PDCD4 counteragent miR-21, a pro-oncogenic micro-RNA, is described as an anti-inflammatory agent. The authors of this research article provide evidence that mice lacking PDCD4 are protected from the lethal effects of lipopolysaccharide (LPS). This report also confirms miR-21 as a negative regulator of PDCD4 expression after LPS stimulation. Downstream mediators of the pro-inflammatory activity of PDCD4 include IL-10, an anti-inflammatory cytokine that is negatively regulated by PDCD4, and IL-6, a pro-inflammatory cytokine that appears to be upregulated in a PDCD4 dependent manner, possibly through an increase in NF-κB activity. Is it possible that a tumor-suppressor protein and an oncogenic micro-RNA can be oppositely targeted to control inflammatory disease?